Microfinance Management System: Logistic 1: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A Microfinance Management System: Logistic 1 is essential for managing the items andequipment stored in RGBC's inventory. The whole procedure of tracking and monitoring issimplified through an online system. The Microfinance Management System: Logistic 1enables RGBC company to handle data and monitor reports efficiently. This system reducestime, eliminates the need for human record-keeping, and lowers mistake rates. Thedevelopers provide the system that satisfies the company's needs, enhances themanagement of the company's project, and improves the monitoring of the items andequipment in the company.Creating a Microfinance Management System: Logistic 1 brings several constraints andobstacles during implementation. The main challenges encountered during the developmentof the system were: There was an error in the code creation. Thus, the system needs to befixed; this requires more focus on creating the system and also teamwork. Another challengeis integrating the microfinance management system: logistic one into other sub-systems of themicrofinance system. The process may require significant resources and technical expertiseto ensure that the System functions smoothly and effectively with other IT systems. Overall,Microfinance Management System: Logistic implementation can present several challenges,but with careful planning and coordination, these can be solved.Implementing this system improved the operations and functionality of the logisticsdepartment. The goals achieved after finishing the Microfinance Management System:Logistic 1 are efficient monitoring of the ongoing and finished project and correctly andefficiently monitoring or tracking the files, documents, and items that enter our system. Thedevelopers were confident that the system would have a better process and be usedappropriately without error.
Keywords: IT & Management